Pengaruh Pengolahan Tanah dan Pemberian Mulsa Organik Terhadap Kesuburan Tanah dan Hasil Produksi Jagung Manis (Zea mays saccaharata Strut L) - Sayyid Hasibuan; Sumihar Sumihar; Siti Mardiana (Universitas Medan Area, 2022)
Sweet corn (Zea mays saccaharata Strut L.) is one of the most staple food crops and has been demanded for decadest. Sweet corn has a great opportunity to be developed because it can be one of the main sources of carbohydrates and protein. One of the causes of the low production of sweet corn is the decrease in soil productivity due to nutrient leaching by rainwater, improper soil management, and soil fertility. This research was conducted by purponing a Split Plot Design of 2 treatment factors, namely; (1) Soil tillage factor (P) consists of 2 levels, (P1 = Minimum Soil Tillage and P2 = Intensive Soil Processing), (2) Organic Mulch (M) consists of 6 levels, M0 = No Mulch, M1 = Plastic Mulch, M2= Rice Straw Mulch, M3= Cocopeat Mulch, M4= Sawdust, M5 = Rice Husk Mulch. The results of this study indicated that the M2 treatment of rice straw mulch has a tendency to increase soil fertility and has significant effect on plant vegetative growth as production. Tillage was no significantly affect soil fertility and plant vegetative growth as production of sweet corn.